Buddhist Leadership In Educational Organization Development - Nyoto; Wiryanto; Hartono, Wira Jaya; Wijoyo , Hadion (Commercium : Journal of Business and Management, 2023)
The purpose of this study was to determine the implementation of Buddhist leadership in the development of educational organizations at the Dharma Loka School and the Metta Maitreya School in Pekanbaru. This study uses a descriptive qualitative method of analysis. Data were collected through observation, documentation studies, and interviews. The informants in this study were the principals, eight informants (including up to 16 teachers and employees), and four Buddhist religious leaders. The data coding of the results of this study used Atlas.ti9 software. The results showed that the leadership of Buddhism has not been implemented optimally at the Dharma Loka school and the Metta Maitreya school in Pekanbaru. This is because the principal has not fully understood the concept of Buddhist leadership. The leadership of Buddhism is believed to be able to improve the development of educational organizations at the Dharma Loka school and the Metta Maitreya school in Pekanbaru if implemented seriously.